KARAKTERISTIK DAN POTENSI BIOETANOL DARI NIRA NIPAH (Nypa fruticans) UNTUK PENERAPAN SKALA TEKNOLOGI TEPAT GUNA - Sopyan Hadi; Thamrin Thamrin; Syaiful Bahry; Setyo S. Moersidik (Jurnal Ilmu Lingkungan, 2013)
Implemetasi underdeveloped research for large-scale production of energy self-sufficient villages and confined in a laboratory scale. The presence of mangrove forests alongthe palm beach pesIsir Indonesia is a potential independent village granaries Energy (DME)to produce local non-fossil energy resources, namely bioethanol as an energy mix throughthe substitution of fossil fuels in order to add and save energy nationwide. Exploration ofgreen energy production process Tempatan with scale appropriate technology is essential toknow the characteristics and potential of bioethanol and fuel substitution products will beproduced. The purpose of this study was to determine the characteristics of bioethanol frompalm sap processing to scale the application of appropriate technology and the potentialvalue of bioethanol FGE levels that would result in a 1 ha of mangrove forests nypa.Research using experimental and observational methodologies. Palm sap is used as thesubject of this study is the result of tapping mangrove palm bunches done processingfermentation, distillation and dehydration. Data collected includes data 1). Characteristic,among others: fermentation, Kadar Alcohol Distillation and Dehydration results TTG Tools,Redemen Bioethanol, Nipah Bioethanol Quality Testing Specifications for Substitute GradeFuel, Bioethanol Blending Testing FGE The substitution process to Fossil Fuels andCounting Bioethanol substitution needs to Biopremium octane FGE 92-95. And data 2). Thepotential value of Bioethanol and Biopremium Nipah. Furthermore, the data obtained andanalyzed, if there is a significant difference followed by Duncan test at 5% significance level.The results showed the characteristics of bioethanol from palm sap processing to scale the application of appropriate technology for fermentation derived average fermentation time isbetween 75.3 to 78 hours, or about 3 days, the average alcohol content of 81.3% obtained bydistillation and 93% as much as 2 times the process and result of dehydration reached 100%for the first time, redemen bioethanol by 8.1%, or a ratio of 12 Litre fermenting juice: 1 Literbioethanol FGE, quality testing specifications nypa fuel grade ethanol to substitute ethanolcontent nypa production equipment amounted to 99.56% TTG already qualified ISOstandards, testing FGE in the bioethanol blending into fossil fuel substitution showed ahomogeneous mixing and calculating FGE bioethanol substitution needs to biopremium 92octane produces a ratio of 1% use 95-octane bioethanol to produce ratio of 2% use ofbioethanol. Furthermore, the potential for the production of bioethanol from palm mangroveforest area of 1 ha with the highest value of 13179.43 liters / ha / year and the lowest value of2744.17 liters / ha / year. Biopremium production potential for the substitution of 10%obtained the highest value and the lowest value of 137,298.50 658,971,50 Liter.